Science news - Crammer, J.L. (England Penguin books, 1950)
These books aimed to present scientific discoveries in a clear and accessible way for a general audience. The series included various volumes covering different areas of science, such as "Astronomy Today". The books were published by Penguin Books, a publisher known for making literature accessible to a wider readership.
Keywords: Theory of physics; History of science; natural science